Propuesta para la gestión del riesgo ambiental y ocupacional en los análisis de jabón cosmético realizados por los laboratorios de la industria de manufactura de jabón (2014)
In the current cosmetic industry, the determination of the soap content is carried out by the method ASTM D-460 (Standard Test Methods for Sampling and Chemical Analysis of Soaps and Soap Products). This method generates a large amount of hazardous waste that requires adequate disposal to reduce its impact on the environment. Furthermore, the exposure of workers to the handling of chemical substances can cause harmful effects to health if adequate corrective or preventive actions are not taken. The purpose of this work is to propose a proposal for the change of the method of analysis to determine the soap content, which is attractive to the cosmetic industry in terms of cost reduction, reduction of environmental impacts, hazards and health risks, and thus improve the efficiency of the areas of quality control that perform this type of analysis. The methodologies used to develop this project were: Standard GTC 45 version 2010 for hazards and labor risks, qualitative and quantitative criteria of Vicente Conesa-Fernández (2010) with modifications by Miguel Ñngel Gamboa Castellanos to determine environmental aspects and impacts, cost analysis , use of the MINITAB 15 software to carry out the statistical analysis and graphs and comparative tables of costs, environmental impacts and labor risks. Within the developed project it was found that when changing the method of analysis from ASTM D-460 to ASTM E-168 they are reduced hazards by 83%, avoids the use of glassware, acids, bases, hot liquids and equipment with hot surfaces that can generate cuts, burns, gas inhalations, irritations on the skin or respiratory tract; possible significant health effects are prevented, such as nervous system affectation, burns, carcinogenic and mutagenic effects, intoxications, etc .; It is reduced from the analysis time by the ASTM D-460 method from 50 min to 5 min by the ASTM E-168 method implying a significant improvement in the efficiency of the resources of the quality control areas. In the environmental analysis the component where there was a common influence on the generation of negative environmental impacts was atmospheric. The use of reagents in the laboratory to carry out the methods causes atmospheric emissions that may be irreversible in some cases due to their degree of toxicity, causing a decrease in air quality. However, ASTM E-168 reduces by 6.46 times the valuation of the atmospheric component with respect to ASTM D-460, being the first method in more favorable mention in the reduction of negative environmental impacts related to the air resource. The ASTM D-460 method has significant effects on the environmental components and has an impact on the sum of all negative environmental components, being 14.65 times higher than the ASTM E-168 method. The ASTM E 168 method has greater advantages, due to the fact that it requires less investment in chemical reagents, does not require water consumption and requires less investment in time to perform the test, which reduces the unit cost of the hand. works and increases the number of tests in a work month (9 times more). Additionally, the sale price is 20.32 times lower in the use of infrared spectroscopy compared to the conventional method taken in this case study for comparison (ie, ASTM D-460). From the integrated QHSE perspective, the ASTM method E-168 is a more feasible proposal than the ASTM D-460 method, because it generates less impacts to the environment, reduces the amount of hazards presented in laboratory tests (ie, in this case, soap determination tests), It is faster to execute and generates operationally less costs and more profits to any type of organization that chooses to carry out this type of economic activity. Finally, it is important to constantly deepen the studies related to the environmental impacts associated with obtaining, transforming and entry into the productive chain of materials and supplies used in the two exposed methodologies, as well as the collection and final disposal of resi dangerous duos generated by the methods studied in this work of degree, in order to have a greater scope and achieve a more profound evaluation of the implications of this type of methods on water, flora, fauna, soil, air, the landscape and the human being.